ANALISIS PENGEMBANGAN LAYANAN KEBIDANAN KOMPLEMENTER TERINTEGRASI DI KABUPATEN TANGERANG PROVINSI BANTEN - Wahidin (Prosiding Seminar Nasional Berseri, 2020)
Today’s public health needs are increasingly complex and the cost of health services is higher while people’s purchasing power is declining, and in the end the community is looking for other alternatives to get health. The above phenomenon spurs health care providers including midwifery services to develop services that meet the needs of quality and affordable communities. The services developed today are a combination of conventional and complementary midwifery services. The practice of complementary midwifery services has become an important part of current midwifery practice. This condition is a separate phenomenon for observation and research, especially in the development of integrated complementary midwifery services in Tangerang Regency, Banten Province. This study aims to analyze the Development of Integrated Complementary Midwifery Services in Tangerang Regency, Banten Province. This research is a non-experimental design, this research is precisely to use survey methods, data processing using a combination of embedded Concuren models between quantitative and qualitative approaches. Presenters Data on the results of the study are presented in the form of frequency distributions and quotations from interviews. The results of complementary midwifery service research have been carried out by 46.7% of midwives with 42.9% of the age range between 26-41 years, 31.4% have D3 Midwifery education and 34.3% have practiced complementary service practices for less than 10 years. an average midwife of 1.72 and an average level of public knowledge of 1.47, the results of the corellation test of 0.524 with a sign of 0,000 showed a positive and significant relationship, the probability value of 0,000 <0.05 in this connection there was clearly a difference between the level of knowledge of the midwife and the community towards developing complementary midwifery services, the dominant developing complementary midwifery services in Tangerang Regency are massage, yoga and hypnotherapy.